Regulatory Risk: Economic Principles and Applications to Natural Gas Pipelines and Other Industries - Kolbe, A. Lawrence; Tye, William B.; Myers, Stewart C.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 1993)
It is common to assert that utility investors are compensated in the allowed rate of return for the risk of large disallowances, such as arise for investments found imprudent or not `used and useful'. However, this book develops a new theory of asymmetric regulatory risk that shows that infallible estimates of the cost of capital are sure to provide downward-biased estimates of the necessary allowed rates of return in the presence of such regulatory risks. The book uses the new theory of regulatory risk to understand recent developments in the risk of natural gas pipelines and other regulated industries.
1: Introduction -- 2: The Theory of Regulatory Risk -- Economic Groundwork -- Economic Implications of Duquesne -- Regulatory Responses To Duquesne -- 3: Regulatory Risk: Objections to the Theory -- Responses to the Objections to the Conceptual Framework -- Responses to Objections to Applications of the Concepts -- Responses to Objections to our Policy Recommendations -- Conclusions -- 4: Sources of Asymmetric Risk in Regulated Industries -- Capital Charges Under Regulation and Competition -- Other Rate-Regulated Industries -- Risks That do and do not Affect the Cost of Capital -- Asymmetric Risk and the Allowed Rate of Return -- Conclusion -- 5: Risk of the Interstate Natural Gas Pipeline Industry: Summary -- Background -- Risks Facing Natural Gas Pipelines for the 1990s -- Regulation and Competition -- Prospects -- Policy Issues -- 6: Recent Trends in the Interstate Gas Pipeline Industry -- Background -- Two Views of Pipeline Risk -- Summary of Findings -- The Changing Pipeline Industry: Financial Trends -- Other Trends -- Conclusion -- 7: Two Views of Pipeline Risk -- The View That Risk is High -- Arguments for Low Risk -- The Risk Analysis to Come -- 8: Risk Analysis for Natural Gas Pipelines -- (3z(BIt$1 (Bs Obvious That Pipelines are Very Risky(3y (B-- (3z(BNo, It$1 (Bs not Obvious at All,(3y (Band (3z(BThose Responses Don$1 (Bt Stand up(3y (B-- Conclusions on the Level of Risk -- 9: Two Fundamental Questions -- (3z(BWhen You Stop Making New Investments, Then We$1 (Bll Start to Worry(3y (B-- Is the Current System Sustainable? -- Is the Current System Desirable? -- The Consequences of Inaction -- Appendix A: Risks That Affect the Cost of Capital -- Risk and Security Prices -- Total Volatility as a Risk Measure -- Diversification as a Way to Reduce Risk -- Business Versus Financial Risk -- Summary -- Appendix B: Summary of Recent History of the Interstate Natural Gas Pipeline Industry -- Basic Structure of the Gas Industry -- Risk Allocation Before Order no. 380 -- The Reallocation of Risk After the Elimination of Minimum Bills -- Effects of Open Access Transportation on Risk Allocation -- Rate Design and Risk Allocation -- Gas Inventory Charges (GICs) -- Conclusion.s
Keywords: Industrial organization; Environmental management; Finance; Industrial Organization; Environmental Management; Finance, general